1990
DOI: 10.1002/aic.690360209
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model for the interaction of caustic reagents with acidic oils

Abstract: This paper describes the mechanisms and a quantative analysis of the interaction between a multicomponent acid mixture with a spectrum of caustic solutions. A physico-chemical model of the acidic oil /caustic system has been proposed which demonstrates the effect on dynamic interfacial tension (IFT) of variations in caustic concentration as well as changes in the initial composition and ionization properties of the constituent acids of the oleic phase. The model relies on the Langmuirian theory of interfacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A number of petroleum researchers have investigated the dynamic IFT behavior of crude oils or synthetic oil-acid mixtures contacted with alkaline solutions (35, 39, 5559). The basic mechanisms described in these studies are as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of petroleum researchers have investigated the dynamic IFT behavior of crude oils or synthetic oil-acid mixtures contacted with alkaline solutions (35, 39, 5559). The basic mechanisms described in these studies are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate explanation relates to the presence of multiple acidic species within the tar. Chiwetelu et al (55) showed that the dominant interfacially active species changed from a higher solubility, lower pK a acid to a less soluble, higher pK a acid as NaOH concentration was increased. A more recent study (37) found that higher molecular weight petroleum acid fractions required a higher alkaline concentration to produce an IFT reduction, but resulted in much less time-dependent IFTs as compared to the lower molecular weight fractions.…”
Section: Discussionmentioning
confidence: 99%
“…The additional oil recoveries increased significantly during the Pickering emulsion flooding followed by chase water flooding as compared to the SP flooding (Table 4, Figure 8 and 9). Previous studies showed that the recovery of oil using conventional surfactant based flood decreased due to the inactivity of surfactant species leading to increase in IFT between crude oil and flood system (Cambridge et al, 1989;Chiweteiu et al, 1990). It is possible that only small part of the surfactant from the conventional chemical flood may participate in EOR due to their affinity for the water phase.…”
Section: Effect Of Temperature On the Oil Recoverymentioning
confidence: 97%
“…For comparison purposes, Figure 5 has been included to show the transient IFT behavior for one representative case in which the oil-phase viscosity is altered by addition of polystyrene. The data in Figure 5 correspond to a similar oil phase (i.e., 10 m M linoleic acid in toluene) and the same NaOH concentration (i.e., 25 mM) as in Figures 3 and 4. Toluene was employed instead of parafin oil in this case since polystyrene is insoluble in the latter.…”
Section: Viscositymentioning
confidence: 98%